EXPLORING THE HOME AND SCHOOL BASED STRATEGIES FOR CHILDREN WITH CEREBRAL PALSY: A PHENOMENOLOGICAL STUDY - Amber Baseer; Majeed, Asma; Nazir, Arooj; Khawar, Rabia (Journal of Pakistan Psychiatric Society, 2022)
OBJECTIVE The present study aimed to explore the strategies which can be used by parents and teachers to facilitate their CP child at home and school. STUDY DESIGN Phenomenology research design was adopted for this research. PLACE AND DURATION OF THE STUDY Participants were recruited from special education schools of Lahore over a period of 6 months from August 2018 to February 2019. SUBJECTS AND METHODS The sample of this study comprised of six child psychologists working with CP children. For the present study six in-depth interviews were conducted with psychologists. After the in-depth interviews were conducted they were transcribed in Urdu. Interpretive Phenomenological analysis was used to analyze the data. RESULTS Two set of themes emerged from the analysis which included the strategies that can be used by parents and teachers to facilitate their CP child at home and school. CONCLUSION The findings of the study also highlighted the strategies that can be used by teachers and parents to provide a better environment to the children with Cerebral Palsy. Separate strategies for parents and teachers were suggested. The parental strategies theme further have five sub-ordinate themes namely; attitude of parents, attitude of siblings, attitude of extended family, home environment and home based interventions. The teacher level strategies further has nine sub-ordinate themes namely; attitude of teachers, attitude of class fellows, teaching techniques, curriculum modifications, classroom modifications, use of assistive technology, vocational training, collaborative team work and counseling.